1979
DOI: 10.1212/wnl.29.11.1509
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations of phensludmide, methsuximide, and their metabolites in relation to clinical efficacy

Abstract: The clinical efficacy of phensuximide and methsuximide was studied in relation to plasma concentrations of these compounds and their desmethyl metabolites. Single- and chronic-dose studies of each drug were carried out in five patients with intractable seizures. Patients were evaluated before and during treatment by 6-hour simultaneous video and telemetered electroencephalographic recordings to characterize the seizure type and by daily determinations of plasma antiepileptic drug concentrations. Phensuximide h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…MPS is an N-demethylated active metabolite of methsuximide (Celontin, Parke Davis) (Strong et al, 1974;Porter et al, 1979) that is effective in the control of petit mal epilepsy. It is more toxic than ES (Chen et al, 1963), but has a broader spectrum of action, being also effective against complex partial seizures (Wilder & Buchanan, 1981;Browne et al, 1983).…”
Section: Drug Concentrations and Methods Ofapplicationmentioning
confidence: 99%
See 1 more Smart Citation
“…MPS is an N-demethylated active metabolite of methsuximide (Celontin, Parke Davis) (Strong et al, 1974;Porter et al, 1979) that is effective in the control of petit mal epilepsy. It is more toxic than ES (Chen et al, 1963), but has a broader spectrum of action, being also effective against complex partial seizures (Wilder & Buchanan, 1981;Browne et al, 1983).…”
Section: Drug Concentrations and Methods Ofapplicationmentioning
confidence: 99%
“…It is more toxic than ES (Chen et al, 1963), but has a broader spectrum of action, being also effective against complex partial seizures (Wilder & Buchanan, 1981;Browne et al, 1983). Clinically relevant free serum concentrations of MPS are in the range of 50-250uM (Strong et al, 1974;Porter et al, 1979), while those for ES have been found to be 250-750juM (Browne et al, 1975). We applied MPS (Sigma, St. Louis, MO, U.S.A.) and ES (a gift of Parke Davis, Ann Arbor, MI, U.S.A.) in a concentration range of 10pM to 10pM to explore fully the dose-dependence of the LTCC reduction by these agents.…”
Section: Drug Concentrations and Methods Ofapplicationmentioning
confidence: 99%
“…All drug solutions were freshly prepared daily. In order to explore the full concentration-dependence of the effects on GABA, concentration ranges of MPS (Sigma, St. Louis, MO, U.S.A.) and ES (a gift of Parke-Davis, Ann Arbor, MI, U.S.A.) were chosen to overlap and extend those which are achieved as free serum concentrations in patients medicated with the anticonvulsant: 50-250paM for MPS (Strong et al, 1974;Porter et al, 1979;Browne et al, 1983), and 250-750puM for ES (Browne et al, 1975). Free serum concentrations of the convulsant TMS (ICN Pharmaceuticals, Plainview, NY, U.S.A.) have not been studied.…”
Section: Drug Concentrations and Methods Ofapplicationmentioning
confidence: 99%
“…The antiepileptic drug methsuximide is rapidly demethylated to N-desmethylmethsuximide, which is also called MPS. Therapeutic plasma levels of MPS in well controlled patients range between 10 and 40 g/ml or 50 and 200 M (Strong et al, 1974;Porter et al, 1979;Wilder and Buchanan, 1981). The sensitivity of human T-type channels to block by MPS was measured as above.…”
Section: Antiepileptic Drug Block Of Human T-type Channels 1123mentioning
confidence: 99%